Status of Insurance of Liability of Operator of Nuclear Installation in International Conventions on Nuclear Civil Liability and legal Order of Iran - S R. Pishrobat (مجله علوم و فنون هسته‌ای, 2018)
According to International Conventions on Civil Liability for Nuclear Damage, The Operator of Nuclear Installation is Obliged to provide Insurance or Other financial Gaurantees for its liability. Making Oblige the Operator of Nuclear Installations is one of the Non derogable and Non Reservable Rules of the Said Conventions. The States Intends to Accede to these Conventions may not Make any Reservation With Respect to those Provisions of the Conventions Relate to Obligation of Operator to provide Insurance for Its liability or adopt National laws or regulations contrary to this obligation. This is while that in Legal Order of Iran There exist no special law or Regulations Concerns to Oblige the Operator of Nuclear Installation to provide Insurance for Its liability. If Iran is Decided to Accede to these conventions It Shall oblige the Operator of Nuclear Installations to provide insurance for its liabilit.